Emerging cocatalysts in TiO2-based photocatalysts for light-driven catalytic hydrogen evolution: Progress and perspectives. (1st January 2022) - Xia, Changlei; Hong Chuong Nguyen, Thi; Cuong Nguyen, Xuan; Young Kim, Soo; Nguyen, Dang Le Tri; Raizada, Pankaj; Singh, Pardeep; Nguyen, Van-Huy; Chien Nguyen, Chinh; Chinh Hoang, Van; Van Le, Quyet
Graphical abstract: Highlights: Cocatalysts in TiO2-based photocatalysts are highlighted for solar hydrogen production. Design strategies of cocatalysts in TiO2-based photocatalysts are presented systematically. Enhancements are attributed to manipulating the charge separation and surface reactions. Challenges and perspectives of cocatalysts in TiO2-based photocatalysts are proposed. Abstract: TiO2 -based photocatalysts have been maintained as the most prominent candidate for solar-driven hydrogen (H2 ) evolution over the past decades. However, poor separation of generated electron-hole pairs has been considered the bottle-neck issue, restricting the TiO2 activity. Coupling a TiO2 photocatalyst to cocatalyst(s) turns out to be the ideal strategy to suppress the charge recombination and offer robust active centres, boosting the H2 evolution performance. This review aims at providing the frontier investigations of cocatalysts-integrated TiO2 for photo-induced H2 evolution. Four types of cutting-edge development of cocatalysts, including metal (noble metal, non-noble metal, bimetallic), metal sulfides and metal phosphides, 2D-MXenes, and dual materials-based cocatalysts, have been successfully highlighted and discussed. The systematically provided cocatalysts, which remarkably promote the charge separation and facilitate the surface reactions, bring out a roadmap to inspire the preparation of superior TiO2 -based materials for H2 evolution shortly. We expect this review could provide enriched information to tailor the TiO2 supported active sites of cocatalysts for highly photo-induced H2 evolution.